2009
DOI: 10.1063/1.3204976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface alloying and orientation on work function of MoTa metal gate

Abstract: Work functions of sub- and monolayers Mo on metal Ta of various orientations are investigated using first-principles methods based on density functional theory. The calculated results reveal that the work function has strongly orientation dependence. However, for a given surface orientation, the work function is insensitive to distributions of Ta/Mo atoms in the surface layer. Moreover, it is found that work functions of the (100) and (111) surfaces increase with increasing Mo composition in the surface layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…This indicates a low anisotropy in the VWF, in contrast with results obtained for the Mo-Ta (bcc) system. 30 When the different atomic terminations are considered, the following trends appear: in general, the Pt termination behaves similarly to the mixed termination, while the Al termination (where possible) shows a lower VWF, which is the lowest VWF possible for a given structure. In other words, this means that Pt atoms at the surface are more dominant than Al atoms in determining the VWF.…”
Section: B Calculation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates a low anisotropy in the VWF, in contrast with results obtained for the Mo-Ta (bcc) system. 30 When the different atomic terminations are considered, the following trends appear: in general, the Pt termination behaves similarly to the mixed termination, while the Al termination (where possible) shows a lower VWF, which is the lowest VWF possible for a given structure. In other words, this means that Pt atoms at the surface are more dominant than Al atoms in determining the VWF.…”
Section: B Calculation Resultsmentioning
confidence: 99%
“…Another approach to simplify the problem was suggested by Xu et al, 30 which allowed avoiding the possibility of phase Recently, an analytical model of the WF composition dependence of solid solution alloys was proposed 32 and was followed by a detailed experimental study of the Hf-Ni system on HfO 2 . 33 The Hf-Ni alloy features solid state amorphization (SSA), and its EWF was found to depend strongly on the surface enrichment of Hf at its interface with the dielectric, rather than on the average composition of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The surface calculations were performed on a slab model. 26 Convergence test with respect to the slab thickness was carried out with a 1 Â 1 surface unit cell. It was found that a slab of 12.1 Å is sufficient to get a converged surface energy for the low energy (010) surface termination.…”
Section: Methodsmentioning
confidence: 99%
“…However, both binary systems exhibit very small mutual solubility and therefore the results cannot be verified by experiment. 12 Xu et al 13,14 used a similar technique with the generalized gradient approximation and projector augmented wave pseudopotential for Ni-Pt and Mo-Ta binary systems. Since the solute atoms in all calculations were concentrated only in the surface atomic monolayer, a comparison with experiments might be difficult for these systems.…”
Section: Introductionmentioning
confidence: 99%